5′‐N‐ethylcarboxamidoadenosine is not a paralog‐specific Hsp90 inhibitor. (4th October 2016) - Liu, Shanshan; Street, Timothy O.
Abstract: The molecular chaperone Hsp90 facilitates the folding and modulates activation of diverse substrate proteins. Unlike other heat shock proteins such as Hsp60 and Hsp70, Hsp90 plays critical regulatory roles by maintaining active states of kinases, many of which are overactive in cancer cells. Four Hsp90 paralogs are expressed in eukaryotic cells: Hsp90α/β (in the cytosol), Grp94 (in the endoplasmic reticulum), Trap1 (in mitochondria). Although numerous Hsp90 inhibitors are being tested in cancer clinical trials, little is known about why different Hsp90 inhibitors show specificity among Hsp90 paralogs. The paralog specificity of Hsp90 inhibitors is likely fundamental to inhibitor efficacy and side effects. In hopes of gaining insight into this issue we examined NECA (5′‐ N ‐ethylcarboxamidoadenosine), which has been claimed to be an example of a highly specific ligand that binds to one paralog, Grp94, but not cytosolic Hsp90. To our surprise we find that NECA inhibits many different Hsp90 proteins (Grp94, Hsp90α, Trap1, yeast Hsp82, bacterial HtpG). NMR experiments demonstrate that NECA can bind to the N‐terminal domains of Grp94 and Hsp82. We use ATPase competition experiments to quantify the inhibitory power of NECA for different Hsp90 proteins. This scale: Hsp82 > Hsp90α > HtpG ≈ Grp94 > Trap1, ranks Grp94 as less sensitive to NECA inhibition. Because NECA is primarily used as an adenosine receptor agonist, our results also suggest that cell biological experiments utilizing NECA may have confounding effects from cytosolic Hsp90 inhibition.